The Indian Pharmaceutical Industry; Evolution of Regulatory System and Present Scenario: Challenges and Opportunities in the Indian Pharmaceutical Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian pharmaceutical industry evolved in true sense only after independence. India is the fourth largest generic pharmaceutical market in the world. Ranking fourth in terms of volume and thirteenth in terms of value in global pharmaceutical markets and is consistently growing. Proper regulatory system ensures the quality, safety and efficacy and standard of medicinal product for sales, importing and manufacturing. India’s pharmaceutical industry is one of the most highly regulated industries in the country. Understanding the regulatory scenario is extremely crucial due to the rapid and ongoing changes and due to the burden on the regulatory bodies to ensure a healthy supply of quality drugs at affordable prices to the Indian masses. India’s pharmaceutical market was dominated by Western MNCs that controlled between 80 and 90 percent of the market primarily through importation. Approximately 99 percent of all pharmaceutical products under patent in India at the time were held by foreign companies and domestic Indian drug prices were among the highest in the world. According to industry estimates, a great chunk --almost 40 per cent --of machinery used in the pharmaceutical manufacturing in India. This creates a very good local and global opportunity for Gujarat in the manufacturing of pharmaceutical machinery, given its strong and well established engineering sector India. The strong growth prospects of the pharmaceutical exports segment and growing demand from the domestic market, will further fuel growth in the pharmaceutical machinery sector. However, Gujarat's engineering sector is highly fragmented, especially the Pharma-machinery manufacturing segment. Due to the highly fragmented nature, there is a dearth of pricing power and critical scale. This in turn restricts the ability to produce the technology-driven products required for operating in global markets.